2012
DOI: 10.1007/s10018-012-0030-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the break-even price for forest protection in Central Kalimantan

Abstract: This paper estimates the break-even price in Central Kalimantan province, Indonesia and evaluates the effectiveness of a REDD? mechanism in this area. On the basis of data collected through a field survey, we found that the break-even price is $15:45 per ton of carbon or $4:21 per ton of carbon dioxide. The figure can be even lower when we take the peat thickness of the area into account. Our analysis shows that the current level of carbon price can provide adequate compensation for Indonesian farmers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 10 publications
1
17
0
1
Order By: Relevance
“…$2.85/t CO 2 e in Cameroon, discounted at 5% (Bellassen and Gitz, 2008) and $4.21 in Indonesia, discounted at 10% (Yamamoto and Takeuchi, 2012). Other studies in Indonesia have reported higher values for oil palm companies and governments.…”
Section: Opportunity Cost Of Avoided Deforestationmentioning
confidence: 89%
See 1 more Smart Citation
“…$2.85/t CO 2 e in Cameroon, discounted at 5% (Bellassen and Gitz, 2008) and $4.21 in Indonesia, discounted at 10% (Yamamoto and Takeuchi, 2012). Other studies in Indonesia have reported higher values for oil palm companies and governments.…”
Section: Opportunity Cost Of Avoided Deforestationmentioning
confidence: 89%
“…This is a conservative estimate that would apply to relatively shallow peat soils. Depending on depth the carbon content of peat soils could be much higher and therefore result in lower carbon prices (Yamamoto and Takeuchi, 2012).…”
Section: Economic Analysismentioning
confidence: 99%
“…We collected the percentages of rice, rubber and oil palm in expanding agricultural land via field survey in 2010 in research area. Yamamoto and Takeuchi (2012) collected socioeconomic data via a field survey in 2010 and 2011 by visiting 211 households, including one-time net revenue from logging per hectare, net revenue from rubber plantations per hectare, price of rice and rubber. Net revenue from oil palm plantations per hectare is from the work by Fairhurst and McLaughlin in 2010.…”
Section: Methodology For Constructing Mac Curvementioning
confidence: 99%
“…In this study, NPV was calculated based on revenue from four main sources: (I) logging (one-time), (II) rice cultivation, (III) rubber plantations, and (IV) oil palm plantations. The NPV of the community's total revenue was calculated as [42,43]:…”
Section: Opportunity Costsmentioning
confidence: 99%